Penerapan Teknologi Application Programming Interface (API) MikroTik untuk Monitoring Virtual Local Area Network (VLAN) di SMK Al-Munawaroh Cianjur - Aris Suhendra; Deni Suprihadi (Universitas Kebangsaan Republik Indonesia, 2024)
This study aims to enhance network control at SMK Al-Munawwarah Cianjur by implementing MikroTik API technology, focusing specifically on the Control aspect of the PIECES method. This aspect includes user access management, data security, and access control to network resources. The research begins with an analysis of the existing network control system, followed by identifying the need for more effective control mechanisms. To improve network control, a MikroTik API-based solution is developed to optimize VLAN configuration and network monitoring. This solution is implemented with the expectation of addressing existing weaknesses in the network management system, as well as providing greater ease and flexibility in network surveillance and access control. The results of the study demonstrate that the use of MikroTik API significantly enhances VLAN configuration efficiency, user access management, and network monitoring within the school environment. This implementation also successfully improves the security and integrity of data transmitted across the network, creating a more secure and controlled network environment. Thus, the findings of this research can serve as a reference for the development of network control systems in other educational institutions with similar needs.